Positive beliefs about anorexia nervosa and muscle dysmorphia are associated with eating disorder symptomatology. (September 2015) - Griffiths, Scott; Mond, Jonathan M; Murray, Stuart B; Touyz, Stephen
Objective: The ego-syntonic nature of anorexia nervosa means that sufferers often deny their symptoms or experience them as positive or comforting. Positive beliefs about eating disorder symptoms may contribute to the development and/or maintenance of eating-disordered behaviour. To date, however, research in this field has been confined to women and anorexia nervosa. Given increasing scientific interest in muscle dysmorphia, a potential eating disorder with ego-syntonic qualities, there is a need to extend current research to include men and muscle dysmorphia. The present study examined whether positive beliefs about anorexia nervosa and muscle dysmorphia were associated with more marked eating disorder symptoms and explored sex differences in these associations. Method: Male and female university students ( n = 492) read descriptions of a male or female character with clinically significant symptoms of anorexia nervosa or muscle dysmorphia. Participants subsequently answered questions about the characters and completed a measure of disordered eating. Knowledge, personal history and interpersonal familiarity with the conditions were assessed. Results: Results from two simultaneous multiple regressions showed that more positive beliefs about anorexia nervosa and muscle dysmorphia were uniquely associated with more eating disorder symptoms for both male and female participants. Effect sizes for these relationships were medium to large (partial eta-squared = 0.09–0.10). The relationships were not moderated by the sex of the participant, nor the sex of the character. Conclusions: Although preliminary, these findings suggest that, among young men and women, positive beliefs about anorexia nervosa and muscle dysmorphia may contribute to the development and maintenance of these conditions. Some symptoms of muscle dysmorphia may be perceived as ego-syntonic, providing another parallel with anorexia nervosa.